2014
DOI: 10.11113/jt.v69.3409
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of CO2 Form Natural Gas via Gas-liquid PVDF Hollow Fiber Membrane Contactor and Potassium Glycinate as Solvent

Abstract: PVDF hollow fiber membranes were fabricated using Thermally Induced Phase Separation (TIPS) method. Gas-liquid interface is formed at the pore openings adjacent to the liquid. In the membrane contactor module, gas diffuses from the gas side across the membrane and reaches the gas liquid interface where gas is absorbed and then reacted in the presence of solvent such as aqueous sodium hydroxide or amine solutions. Nowadays, Monoethanol amine (MEA) and Diethanolamine (DEA) are the most commonly used solvents. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…They concluded that the efficiency of the composite solution is evidently higher than that of the single glycine salt solution in coupling with hollow fiber membrane contactor. Ghasem et al [19] applied aqueous amino acid salts for CO 2 absorption. It was clearly seen from the results that the performance of CO 2 absorption using PG is always better than MEA and DEA under the identical operating circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the efficiency of the composite solution is evidently higher than that of the single glycine salt solution in coupling with hollow fiber membrane contactor. Ghasem et al [19] applied aqueous amino acid salts for CO 2 absorption. It was clearly seen from the results that the performance of CO 2 absorption using PG is always better than MEA and DEA under the identical operating circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…If a more sophisticated modeling approach is desired for analyzing in detail the mass, momentum, and heat-transfer effects inside the membrane module, 3D software tools such as COMSOL Multiphysics, ANSYS, and OpenFoam [56][57][58] can be used to account for actual module geometry and associated fluid contacting. However, 3D models can be computationally expensive, and therefore simulation times must be balanced with the level of accuracy wanted as the meshing requirements required for the solution to be mesh independent will lead to longer run times.…”
Section: Software Implementationmentioning
confidence: 99%